A genome-wide metabolomic resource for tomato fruit from Solanum pennellii - Perez-Fons, Laura; Wells, Tom; Corol, Delia I.; Ward, Jane L.; Gerrish, Christopher; Beale, Michael H.; Seymour, Graham B.; Bramley, Peter M.; Fraser, Paul D. (Nature Publishing Group, 2014)
Tomato and its processed products are one of the most widely consumed fruits. Its domestication, however, has resulted in the loss of some 95% of the genetic and chemical diversity of wild relatives. In order to elucidate this diversity, exploit its potential for plant breeding, as well as understand its biological significance, analytical approaches have been developed, alongside the production of genetic crosses of wild relatives with commercial varieties. In this article, we describe a multi-platform metabolomic analysis, using NMR, mass spectrometry and HPLC, of introgression lines ofSolanum pennellii with a domesticated line in order to analyse and quantify alleles (QTL) responsible for metabolic traits. We have identified QTL for health-related antioxidant carotenoids and tocopherols, as well as molecular signatures for some 2000 compounds. Correlation analyses have revealed intricate interactions in isoprenoid formation in the plastid that can be extrapolated to other crop plants.